Characterization of thermal decomposition of oxygenated organic compounds in FIGAERO-CIMS. Issue 12 (22nd October 2021) - Yang, Laura Hyesung; Takeuchi, Masayuki; Chen, Yunle; Ng, Nga Lee
Abstract: The Filter Inlet for Gases and AEROsols coupled with a chemical ionization mass spectrometer (FIGAERO-CIMS) measures particle-phase organics via temperature-programmed thermal desorption, though the extent to which different compounds undergo thermal decomposition is not well characterized. We study the effect of functional groups on the degree and pathways (decarboxylation and dehydration) of thermal decomposition in FIGAERO-CIMS using atmospherically relevant alcohols, monoacids, diacids, polyacids, and multifunctional acids. Based on their carbon oxidation state, compounds are categorized as less-oxidized oxygenated organic aerosol (LO-OOA), oxygenated organic aerosol (OOA), or more-oxidized OOA (MO-OOA), and exhibit little, minor, and considerable thermal decomposition, respectively. The result shows that thermal decomposition leads to negative biases in the measured elemental ratios (O:C and H:C) of compounds categorized as OOA and MO-OOA, except for the H:C ratio of those categorized as MO-OOA. We develop screening criteria for considerable thermal decomposition using double bond equivalent (DBE), maximum desorption temperature (Tmax ), and the number of oxygen (nO) (DBE ≥ 2, Tmax ≥ 72 ° C, and nO > 4). Additionally, we find that β -keto-carboxylic acids and carboxyl-containing aromatic compounds are the only compounds that favor decarboxylation. Lastly, we investigate the effect of the instrument's temperature ramping rate (40, 13.3, and 3.3 ° C min −1 ) on the thermal decomposition using citric acid. We recommend using 13.3 and 40 ° C min −1 ramping rates but do not recommend using 3.3 ° C min −1 which acts distinctively from 13.3 and 40 ° C min −1 with the most parental compound decomposition. Copyright © 2021 American Association for Aerosol Research